The Position of Points, Lines and Planes in a Mosque Construction for Geometrical Visualisation - Riza Isna Khoirun Nisa; Rania Nova Dechandra; Wahyuni Eka Maryati; Sri Prihatin Hartati (Ethnomathematics Journal, 2023)
The purpose of this qualitative descriptive study was to identify the concepts of the positions of points, lines, and planes in the building elements of the Kauman Gedhe Mosque foyers such as pillars, ceilings, crossbars and the roof of the building. The research data was obtained from direct observation which was documented using a cellphone camera and visualized with the help of GeoGebra. The results of the study show that there are on the building elements of the Mosque concepts of the position of a point to a line (a point is inside the line and a point is not on the line), a point to a plane (a point is in the plane and a point is outside the plane), a line to a line (two parallel lines, two perpendicular intersecting lines, two non-perpendicular intersecting lines, two coincident lines, and two intersecting lines), a line to a plane (parallel lines, a plane perpendicular, and a plane coincident with a plane), and a plane to a plane (two parallel planes, two non-perpendicular intersecting planes, two perpendicularly intersecting planes, and two coincident planes). Based on the results of this study, it is concluded that there are 16 mathematical concepts found in the Gedhe Kauman Mosque. Visualization of abstract mathematical objects can easily be imagined through cultural sites. This is able to lighten cognitive loads so that it is easy to understand and students are encouraged to construct their own understanding based on the experience they have gained.